Pelatihan Psikoedukasi berbasis Gender dan Inklusi Sosial untuk Mereduksi Kekerasan Seksual pada Konselor Sekolah - Hotifah, Yuliati; Muslihati; Zen, Ella Faridati; Khowatim, Khusnul; Saputra, Nur Mega Aris (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The issue of sexual violence in Indonesia is increasingly rampant and has increased every year. Cases of violence occur among women, adolescents and children. The purpose of this activity is the application of psychoeducation based on gender equality and social inclusion as a method to reduce cases of sexual violence against students. The method applied in this community service activity uses the 6P method, which includes the preparation stage, preparation of materials, introduction, training, closing and reporting. The results of the activity showed that 85% of participants had a high understanding of gender equality and social inclusion as an effort to reduce sexual violence in the school environment. The multiplying impact resulted in a model and module of psychoeducation based on gender and social inclusion as a preventive effort to prevent and reduce sexual violence in schools based on gender and social inclusion.